Descendants [videorecording (DVD)] - Chenoweth, Kristin; Boyce, Cameron; Cameron, Dove; Carson, Sofia (Walt Disney Studios Home Entertainment, 2015)
A present-day idyllic kingdom where the benevolent teenage son of King Adam and Queen Belle offers a chance of redemption for the trouble making offspring of Disney's classic villains: Cruella De Vil (Carlos), Maleficent (Mal), the Evil Queen (Evie) and Jafar (Jay).